The curse of oil: oil resources turned out to be an international security issue / Siti Nurulshakila Ruslan - Ruslan, Siti Nurulshakila (2010)
Oil is an exhaustible resource and yet it has high consumption by all the industry. Oil resources are been use in automobile, manufacturing, cosmetics and even on pharmaceutical product. In that case, many parties from all over the world especially those country that did not directly possessed any oil resources are fighting to get as many as they can. Thus, it cause problem and even worse war among country as they fight for the oil resources. As this issue spread to all over the world and it get worse, it had turn to be an international security issue. In fact the economists often talk of the curse of oil pointing out that countries with resources such as oil often grow more slowly, more corruptly, less equitably, more violently and with more authoritarian governments than others do. The study will focus on oil industry and it linked with the international security issue.